Development of a Bioactive Dental Barrier Membrane Based on PCL/Collagen and PVA/Hydroxyapatite Layers with Amoxicillin-Loaded Electrosprayed Coating - Akkus, Hilal Gulsena Nur; Bingol, Ayse Betul; Oktay, Busra; Ozsan, Buse; Kizilkurtlu, Ahmet Akif; Erarslan, Azime; Ciftci, Fatih; Ustundag, Cem Bulent (MDPI, 2026)
Background/Objectives: Guided bone regeneration (GBR) in dental applications requires scaffolds that possess balanced mechanical strength, controlled biodegradability, and excellent biological performance; therefore, this study aims to develop and evaluate a multilayered biofunctional dental membrane designed to enhance mechanical, biological, and antibacterial performance. Methods: The multilayered membrane was fabricated using sequential electrospinning and electrospraying techniques to form a polycaprolactone (PCL)/Collagen first layer and a polyvinyl alcohol (PVA)/Collagen/Hydroxyapatite (HAp) second layer, topped with a final electrospray coating of PVA/Amoxicillin. Characterization was performed via SEM, FTIR, and EDS, followed by evaluations of tensile properties, swelling behavior, hydrolytic degradation, in vitro drug release, disk diffusion antibacterial activity against Staphylococcus aureus and Escherichia coli, and 7-day L929 fibroblast cytocompatibility (ANOVA/Tukey, p < 0.05). Results: SEM, FTIR, and EDS analyses confirmed uniform nanofiber morphology, homogeneous HAp distribution, and successful integration of bioactive compounds. The membrane exhibited a maximum tensile strength of 15.17 N, strain of 25.24%, and stress of 2.16 MPa, while swelling reached similar to 100% within 2 h and degradation stabilized around 4% weight loss after 48 h. Drug release profiles showed a rapid amoxicillin release in the first 50 min, plateauing at approximately 4.5 mg/L by 350 min, with distinct antibacterial inhibition zones, and the PCL/Col-PVA/Col/HAp-PVA/Amox group demonstrated the highest cell viability (similar to 140%) after 7 days, significantly exceeding the control groups (p < 0.01). Conclusions: These quantitative findings validate the fabricated multilayered membrane's potential as a mechanically robust, biodegradable, antibacterial, and bioactive scaffold for advanced guided bone regeneration in dental applications.
Keywords: biomaterials; dental membrane; electrospinning; electrospray; drug; polymer; COLLAGEN; SCAFFOLD; PVA; HYDROXYAPATITE; ANTIBACTERIAL; HYDROGELS; Pharmacology & Pharmacy